A Study of Pharmaceutical Applications of Hemicelluloses From Nine Food Materials - Irva Waqar; Shazma Massey; Fozia Iram; Mohammad Saeed Iqbal; Naila Perveen; Abdul H. Khan (International Journal of Polymer Science)
Conclusion: Hemicelluloses from natural sources show potential as effective tablet binders, extended-release agents, film-coating materials, and suspending/thickening agents in pharmaceutical formulations. These findings highlight their promise as sustainable and biocompatible alternatives to synthetic/semisynthetic excipients.